THE BEGINNINGS AND DEVELOPMENT OF AGRICULTURAL ADVISORY SERVICES IN POLAND - Józef Kania (Acta Scientiarum Polonorum. Oeconomia, 2017)
The main objective of this article is to present the development of agricultural advisory services in Poland from its beginnings on the Polish lands, until the entry of our country into the European Union (1 May 2004). The data was obtained from a review of literature, published mainly in Polish, hence, not known in English publications and originates from the author’s research carried out in the framework of research grant. The study used a descriptive method and documents the history of agricultural extension dating back to the mid-19th century. In the interwar period (1918–1939), advisory services were carried out by the newly established agricultural chambers, and after World War II, after their liquidation, by state system of agricultural advisory services, which was subject to many changes in the organizational structure and objectives pursued. In the first period of transition of agriculture to a free market economy, the author emphasized the big role of the Polish/American Extension Project for the reorganization of Polish advisory and improvement of skills of our advisers.